Children reading habits and availability of books in Botswana primary schools: implications for achieving quality education (2007)
In an age when browsing the net, playing with funky handsets and passing non-stop SMSs seem to be the order of the day, reading a book in a peaceful comer of a library has become an archaic idea for most people. While technology is slowly taking a steady control over individual lives, the reading habit is fast vanishing into thin air”(The Hindu, 2004:1). The achievement of quality basic education in all countries in Africa call for development of good reading habits of both the children and the adult. This will change the Stigma already associated with Africa as a continent with a “Poor Reading Culture”. This study examined children’s reading habits and the availability of books in Botswana primary schools and considers its implications on the achievement of quality basic education in the country. One hundred and fifty (150) primary school pupils were randomly drawn from ten (10) schools and ten teachers, one from each school were interviewed in two Botswana cities i.e. Gaborone and Francistown. Participants were mainly drawn from Standards 6 and 7. Their ages ranged from 10-13 years with a mean of 11.5 years. A modified questionnaire, “Children Reading Habits/Books Availability Scale” with r = 0.79 cronbach alpha was used to gather data. Six research questions were developed to guide the study, and the results indicate the following: Botswana primary school pupils do not have a good reading habits and have a culture with only 36.7% of them reading on a daily basis; and that of these, most read only textbooks just for the purpose of passing examinations. Those Botswana children (53.3%) read only for 1-2 hours daily; while it was also evident that some even read less than an hour per day. Results further showed that no difference was observed in the perception of Botswana pupils about the availability and accessibility of reading materials in their various schools. Furthermore, it was revealed that the pupils depend largely on the notes given by their teachers as the major source of reading material based on inadequate availability of books. Inadequate book availability, lack of interesting children’s literature, and watching television are identified as factors hindering pupils from developing reading habits. Furnishing primary schools libraries in the country with recent books, getting parents to develop an interest in reading for their children to emulate coupled with the idea that children’s literature should be made available in all primary schools constitute the major suggestions as measures to overcome the problem so that the achievement of quality basic education in the country would not be a mirage. Recommendations based on the results of the study for parents, teachers, schools, mass media and the government are highlighted.